Scaling Analysis of Thermal Energy Evolution in Granites - JIA Peng; XI Baoping; LI Xiaoke; XIE Jin; CAI Jiahao (Taiyuan Ligong Daxue xuebao)
[Purposes] The damage of rocks by thermal action is an extremely common natural and engineering phenomenon. [Methods] The evolution of thermophysical parameters of granite specimens of different sizes cooled in air at laboratory scale is studied from the energy point of view through the cooling method, and the characteristics of energy absorption, release, and dissipation during the whole process of unsteady heat transfer are discussed to reveal the intrinsic connection between the evolution of energy in the unsteady process and the size characteristics of granite specimens. [Findings] The results show that: The specific heat of different sizes and types of high-temperature granite specimens continues to decrease in the process of air cooling to room temperature; In the process of unsteady state heat transfer energy evolution, the magnitudes of the dissipation energy and dissipation ratio of specimens with the same size are positively correlated with the initial high-temperature states; In the unsteady state heat transfer conditions are consistent, with the increase in the volume of the specimen, the absolute value of the energy used for damage is increasing but the relative value is decreasing; With the increase of specimen specific surface, the absolute value of the energy used for damage is decreasing but the relative value is increasing. The results of this study can enrich the development of high-temperature rock mechanics theory.